Sistem Pendukung Keputusan Menentukan Lokasi Bagi Pengembang Rumah Skala Kecil Menggunakan Metode Analytical Hierarchy Process - Yudi Permana; Muhammad Rikar Permana (Teknik Informatika, Universitas Pelita Bangsa, 2018)
In urban department, there are a lot of large scale real estate developers that fulfill the need of housing for the urban society, run as a real estate industry, develop a well-planned concept on large lands and arrange the housing complex as a prospect. But small and micro developers in the other hand should choose well-arrange housing neighborhood as a developing prospect and develop only a single or a few units, whenever the units have been sold out they should find other new locations to be developed, the usage of AHP method helps to find the criterions of sufficient location to be developed.